2007
DOI: 10.1093/ecam/nem096
|View full text |Cite
|
Sign up to set email alerts
|

Herbal Medicine Today: Clinical and Research Issues

Abstract: Herbal medicine is the use of medicinal plants for prevention and treatment of diseases: it ranges from traditional and popular medicines of every country to the use of standardized and tritated herbal extracts. Generally cultural rootedness enduring and widespread use in a Traditional Medical System may indicate safety, but not efficacy of treatments, especially in herbal medicine where tradition is almost completely based on remedies containing active principles at very low and ultra low concentrations, or r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
227
0
5

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 387 publications
(258 citation statements)
references
References 10 publications
1
227
0
5
Order By: Relevance
“…However, in this current work, we found that recommendations of friends and family were the main reasons of CAM use. It was also demonstrated that belief played a major role in its use, as respondents believed that CAM was natural and safer, similar to previous findings (Firenzuoli and Gori, 2007).Among the various CAM used, herbal medicine was most the common choice (Firenzuoli and Gori, 2007), which was representative of the current population. While they recognized its benefits, unfortunately not many were aware that CAM is not without its risks (Wong et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…However, in this current work, we found that recommendations of friends and family were the main reasons of CAM use. It was also demonstrated that belief played a major role in its use, as respondents believed that CAM was natural and safer, similar to previous findings (Firenzuoli and Gori, 2007).Among the various CAM used, herbal medicine was most the common choice (Firenzuoli and Gori, 2007), which was representative of the current population. While they recognized its benefits, unfortunately not many were aware that CAM is not without its risks (Wong et al, 2012).…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, many herbal therapies have become increasingly popular among patients and physicians, and they are now used by approximately 20% of the population in the United States because herbal medicines generally have few side effects and they are very effective [2]. However, concerns have been raised over the lack of quality control and scientific evidence for the safety of herbal medicine [3]. Besides, few scientific studies have explored the safety and toxicity of herbal medicines, so severalwa-rnings have been issued regarding the potential adverse effects of herbal medicines [4], [5].…”
Section: Introductionmentioning
confidence: 99%
“…Rigid controls of vegetal derivatives are of paramount importance because herbs may be corrupted by aflatoxins [5] (or other natural toxic substances), heavy metals (lead, chromium, cadmium, etc. ), or adulterated with undeclared herbs or even with synthetic drugs [6].…”
mentioning
confidence: 99%
“…Since many herbal products on the market have not been thoroughly tested for their pharmacology and toxicology, pharmacovigilance is of paramount importance in detecting unwanted reactions [5,9], because clinical patterns and severity can be highly variable, even for the same product [1].…”
mentioning
confidence: 99%
See 1 more Smart Citation